Risk factors for chronic kidney disease in older adults - Gallardo Romero, Emma; Valido Valdes, Doraimys; Gonzalez Medina, Mariela; Fernandez Rojas, Yoannia Caridad; Vilaú Suárez, Wilman Meylin (Salud Integral y Comunitaria, 2024)
Introduction: Chronic kidney disease is one of the most prevalent diseases worldwide, representing the sixth fastest growing cause of death. Objective: To identify the factors associated with chronic kidney disease in older adults at clinic 61 of the 1ro de Enero polyclinic in the municipality of Consolación del Sur. Method: An applied, descriptive, cross-sectional study was conducted between January 2022 and December 2023 on elderly patients at clinic 61. The universe consisted of 245 patients, with a sample of 245 patients who met the inclusion criteria. Results: The 70-79 age group predominated at 46.1%, males at 60.8%, and white skin color at 64.5%. The most frequent stage of chronic kidney disease was stage II at 37.1%. The most frequent risk factors were high blood pressure (76.3%), followed by diabetes mellitus (19.6%). Conclusions: The risk of developing chronic kidney disease is higher in people with high blood pressure, diabetes, smoking, proteinuria, and close relatives with kidney disease.